2004
DOI: 10.1103/physrevb.70.054414
|View full text |Cite
|
Sign up to set email alerts
|

Effect of extra electrons on the exchange and magnetic anisotropy in the anionic single-molecule magnetMn12

Abstract: To understand the effect of molecular environment on the electronic and magnetic properties of the single-molecule magnet (SMM) Mn 12 , we explore two possible means for adding extra electrons to molecule. We explore both substitution of Mn ions by Fe ions and the inclusion of neighboring electronic donors. For both possibilities we calculate, within density-functional theory, the electronic structure, the total ground-state spin and ordering, the magnetic anisotropy barrier, the transverse magnetic anisotropy… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
52
0

Year Published

2006
2006
2019
2019

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 41 publications
3
52
0
Order By: Relevance
“…Recently, it has been demonstrated that the first excited spin state in a neutral Mn 12 derivative has S n;1 9 and lies about n 4 meV above the S n;0 10 ground state [27], as theoretically predicted by Park and Pederson [28]. Little is known about positively or negatively charged Mn 12 clusters, except that one-electron reduced species have a S n 1;0 9 1 2 ground state and a lower MAB [29].…”
mentioning
confidence: 99%
“…Recently, it has been demonstrated that the first excited spin state in a neutral Mn 12 derivative has S n;1 9 and lies about n 4 meV above the S n;0 10 ground state [27], as theoretically predicted by Park and Pederson [28]. Little is known about positively or negatively charged Mn 12 clusters, except that one-electron reduced species have a S n 1;0 9 1 2 ground state and a lower MAB [29].…”
mentioning
confidence: 99%
“…5. The non-uniaxial terms are not present for the isolated Mn 12 molecule 27 but are due to the lowering of symmetry by the leads. These non-uniaxial terms destroy the conservation of the z component of the molecular spin, S z tot .…”
Section: Introductionmentioning
confidence: 99%
“…Magnetic molecules based on a Mn 12 O 12 core with organic ligands (henceforce Mn 12 ) have a large spin S = 10 in the neutral state and strong easy-axis anisotropy. 5,6,7,8,27 The anisotropy leads to an energy barrier between states with large positive or negative spin components along the easy (z) axis. Mn 12 has been studied intensively with regard to quantum tunneling through this barrier.…”
Section: Introductionmentioning
confidence: 99%
“…32,33 We investigate the MAB by computing the the total energy for a rotation of the spin axis from the z-direction to the x-y plane using a non-self-consistent SOI calculation. The goal is to understand the effects of the supporting graphene on the MAB.…”
Section: Magnetic Anisotropy Barriermentioning
confidence: 99%